2002
DOI: 10.1128/aem.68.5.2161-2171.2002
|View full text |Cite
|
Sign up to set email alerts
|

Novel Plant-Microbe Rhizosphere Interaction Involving Streptomyces lydicus WYEC108 and the Pea Plant ( Pisum sativum )

Abstract: A previously undescribed plant-microbe interaction between a root-colonizing Streptomyces species, S. lydicus WYEC108, and the legume Pisum sativum is described. The interaction is potentially of great importance to the health and growth in nature of this nodulating legume. The root-colonizing soil actinomycete S. lydicus WYEC108 influences pea root nodulation by increasing root nodulation frequency, possibly at the level of infection by Rhizobium spp. S. lydicus also colonizes and then sporulates within the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
204
1
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(228 citation statements)
references
References 54 publications
5
204
1
12
Order By: Relevance
“…Long filamentous and branched structures were also observed in infected cells; however, it was not possible by visual inspection to determine whether these structures were hyphae or pleomorphic bacteriods which, in many cases, enlarge up to seven times from their original bacterial rod-shape size (Oke and Long, 1999;de Maria et al, 2005). Future studies are needed to determine how Micromonospora relates to Bradyrhizobium in a tripartite interaction; a synergistic effect of both bacteria on the plant is possible (Tokala et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long filamentous and branched structures were also observed in infected cells; however, it was not possible by visual inspection to determine whether these structures were hyphae or pleomorphic bacteriods which, in many cases, enlarge up to seven times from their original bacterial rod-shape size (Oke and Long, 1999;de Maria et al, 2005). Future studies are needed to determine how Micromonospora relates to Bradyrhizobium in a tripartite interaction; a synergistic effect of both bacteria on the plant is possible (Tokala et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tokala et al (2002) showed that a Streptomyces strain, WYEC108, was able to colonize the roots of Pisum sativum increasing root nodulation frequency. These authors are of the opinion that these plant-microbe interactions may be common in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Actinobacteria, on the other hand, has recently been associated with disease suppressive soils (Mendes et al, 2011). Streptomyces species, which were significantly more abundant in the vegetative stage of Arabidopsis (Supplementary Figure S4E), are able to increase root nodulation efficiency and promote plant growth of the legume Pisum sativum (Tokala et al, 2002) while simultaneously triggering plant defense in Arabidopsis or apple trees (Cohen et al, 2005;Conn et al, 2008;Lin et al, 2012). On the other hand, Bacteroidetes' role in the rhizosphere has not yet been elucidated but it has been reported that they are important contributors to nutrient turnover in the soil (Yousuf et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces are a group of Gram-positive bacteria, with high G + C content belonging to the order Actinomycetales, which form branched mycelia and hence sometimes been classified as fungi imperfecti. Plant growth promotion potential of Streptomyces was reported on bean (Nassar et al 2003), tomato (El-Tarabily 2008), pea (Tokala et al 2002), wheat (Sadeghi et al 2012) and rice (Gopalakrishnan et al 2012a, b). Streptomyces promote plant growth either by producing indole-3-acetic acid (Aldesuquy et al 1998) or siderophores (Tokala et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth promotion potential of Streptomyces was reported on bean (Nassar et al 2003), tomato (El-Tarabily 2008), pea (Tokala et al 2002), wheat (Sadeghi et al 2012) and rice (Gopalakrishnan et al 2012a, b). Streptomyces promote plant growth either by producing indole-3-acetic acid (Aldesuquy et al 1998) or siderophores (Tokala et al 2002). Streptomyces has also been extensively studied and used for biocontrol of soil-borne fungal pathogens (Mahadevan and Crawford 1997;Trejo-Estrada et al 1998;Macagnan et al 2008.…”
Section: Introductionmentioning
confidence: 99%